Research progress in self-oscillating polymer brushes. Issue 3 (6th January 2022) - Zhang, Bao-ying; Luo, Hai-nan; Zhang, Wei; Liu, Yang
Abstract : Polymer brushes possess unique changes in physical and chemical properties when they are exposed to external stimuli and have a wide range of applications. Abstract : Polymer brushes possess unique changes in physical and chemical properties when they are exposed to external stimuli and have a wide range of applications. Self-oscillating polymers are anchored on surfaces of certain materials and are coupled with some self-oscillating reactions (with the Belousov–Zhabotinsky (BZ) reaction as an example) to form self-oscillating polymer brushes. As an independent field of stimulus response functional surface research, the development of new intelligent bionic materials has good potential. This article reviews the oscillation mechanisms of self-oscillating polymer brushes and their classifications. First, the oscillation mechanisms of self-oscillating polymer brushes are introduced. Second, the research progress in self-oscillating polymers is discussed in terms of the type of self-oscillation reactions. Finally, possible future developments of self-oscillating polymer brushes are prospected.